The Future of Compulsory Dispute Settlement Under The Law of the Sea Convention - Rayfuse, Rosemary (Victoria University of Wellington Law Review, 2005)
In this article Rosemary Rayfuse evaluates the dispute resolution provisions found in Part XV of the United Nations Law of the Sea Convention (UNCLOS). While the cases emerging from the International Tribunal on the Law of the Sea (ITLOS) to date have been limited in number, they can provide us with some idea of whether the Part XV machinery has been successful, and allow some predictions to be made as to its continuing role in the development of the law of the sea. Having examined this jurisprudence, she concludes that while the fears of fragmentation in the sense of inconsistent interpretations or applications of legal rules have not yet materialised, the overall role for the dispute settlement provisions in the development of international law seems rather limited.